Influence of AGTR1 and ABCB1 Gene Polymorphism on the Curative Effect of Irbesartan - Qiao Wang; Lingsen You; Zeyu Li; Leiyi Zhang; Xueqi Li; Xuesong Yang (International Journal of Hypertension)
The interindividual heterogeneity in response to the antihypertensive effect of irbesartan has received considerable attention because of gene polymorphism. In this study, we investigated the new combinational influences of AGTR1 and ABCB1 gene polymorphism on the therapeutic effect of irbesartan among Chinese hypertensive patients. A total of 353 samples including 168 normal people and 185 hypertensive patients were adopted, and genotypes comprise ABCB1 (CC, CT, and TT) and AGTR1 (AA and AC) in this study. The results of multiple linear regression models showed that no statistically significant differences were observed in blood pressure change following irbesartan administration in each genotype from either ABCB1 (CC, CT, and TT) or AGTR1 (AA and AC). However, spline smoothing analysis demonstrated that the blood pressure therapeutic responses of irbesartan presented a noticeable difference among different ABCB1 genotypes when irbesartan doses reached over 300 ng/mL. Eventually, we assumed that the different drug responses of irbesartan among various AGTR1 genotypes were due to the diversity of the irbesartan-conjugated protein, which is responsible for crossing-coupled intracellular G-protein-coupled receptors (GPCRs).